Satisfaction Rates Are Low following Revision Total Knee Arthroplasty in Asians Despite Improvements in Patient-Reported Outcome Measures - Bin Abd Razak, Hamid Rahmatullah; Lee, Jian Hui Merrill; Tan, Shi Ming; Chong, Hwei Chi; Lo, Ngai Nung; Yeo, Seng Jin (The Journal of Knee Surgery, 2019)
With the aging population in Asia and increase in total knee arthroplasty (TKA) utilization rates, the number of patients requiring revision TKA (rTKA) are expected to increase as well. The purpose of this study was to evaluate outcomes and satisfaction rates following rTKA in an Asian population that has unique cultural demands. Registry data of patients who underwent rTKA from 2006 to 2010 and had completed 5 years of follow-up were analyzed. Flexion range, Oxford Knee score (OKS), Knee Society score (KSS), the Short-Form 36 (SF-36), and satisfaction rates were assessed for improvement from preoperative values, as well as by the minimum clinically important difference (MCID) criterion. rTKA was performed in 163 patients. There were significant improvements seen at 2 years postoperatively and these were sustained up to 5 years. The minimal clinically important difference (MCID) criterion for KSS, OKS, and SF-36 physical component score (PCS) was met at 2 and 5 years postoperatively. The overall complication rate was 3.7% at a mean follow-up of 8.4 years. A total of 121 patients (74.2%) were satisfied at 5 years postoperatively. Within our cohort, rTKA results in significantly improved patient-reported outcome measures with a low complication rate of 3.7% at a minimum of 5-year follow-up. Despite these encouraging results, satisfaction rates remain low.
Keywords: total knee arthroplasty; Asian; revision; outcomes; MCID